Do sociodemographic, behavioral or health status variables affect longitudinal anthropometric changes in older adults? Population‐based cohort study in Southern Brazil. Issue 11 (10th May 2017) - Goes, Vanessa Fernanda; Wazlawik, Elisabeth; d'Orsi, Eleonora; Navarro, Albert; González‐Chica, David Alejandro
Abstract : Aim: To assess the influence of sociodemographic, behavioral and health status variables on longitudinal changes in height, weight, and waist circumference in older adults. Methods: This is a population‐based cohort study in Southern Brazil ( EpiFloripa Study) investigating 1702 individuals aged 70.6 ± 8.0 years (62.5% women). Height, weight and waist circumference were measured in 2009/10 and 2013/14 ( n = 1197). Linear mixed regression models were used to estimate age‐related changes in anthropometric measurements according to the explanatory variables. Results: Unmarried individuals, with higher education level or household income, with excessive alcohol consumption, former smokers and positives for some chronic disease were heavier than their counterparts. Similar associations were observed for waist circumference in terms of marital status, smoking and the presence of chronic diseases. Height was higher among the wealthiest, in former smokers and those physically active. Only in men were a lower education level and being unmarried associated with higher weight loss after the age of 75 years, but not with waist circumference reduction. Conclusions: Despite their association with current height, weight and waist circumference, neither behavioral variables nor the presence of chronic diseases influenced the anthropometric changes. Less educated and unmarried men lose weight at a higher rate, showing a higher risk of sarcopenia.Geriatr Gerontol Int 2017; 17: 2074–2082 .